Ethical obligations that arise from the effects of cultural & religious practices and beliefs on the well-being of children with Autism Spectrum Disorder - Simelane, Ayanda Purity (My University, 2022)
Parents of children diagnosed with ASD in South Africa go through a multi-approach pathway to care in search of the best treatment method. This is because ASD is still not clearly understood by many African people.In general, illness in the African culture is often associated with tradition and culture, spiritual forces, witchcraft, family wrongdoings and ancestors to mention a few. Parents and families continue to search for causes and answers for having a child with ASD. Some of these questions include: why did they give birth to a child with ASD, who caused their child to get a disorder such as ASD and how can the disorder of ASD be treated or reversed? Some of these questions may not be answered by allopathic practitioners since the aetiology of ASD is still unknown. The shock of getting a diagnosis of ASD may be overwhelming for many parents. Often, having a child with ASD is still seen as a loss and to some, a child with ASD means a form of punishment from the ancestors or God. It is based on these reasons that parents embark on multiple approaches to treatment for their children which include traditional forms of healing and religiously informed approaches of treatment. Often, when parents seek help for their children, the medical approach is held parallel to other approaches of treatment. This study was a bioethical analysis with an empirical component. The study aimed to explore the ethical obligations that arise from the effects of traditional and religious practices and beliefs on the well-being of children with ASD. Two distinct theoretical frameworks provided the underpinning forthis study. The first framework adopted was Uri Bronfenbrenner’s Ecological Systems Theory on child development. This mostly informed the empirical element of the study. The second theoretical framework was Moral Theoretical Pluralism (Cultural Relativism and Ubuntu), an approach to moral philosophy that rejects the notion that all of our ethical obligations can be explained in terms a single (or monist) theory of right action, in favour of the position that the best arguments for how we ought to act are mostly grounded in several of the recognised moral theories. This framework mostly provided the foundation for the bioethical or normative component of the study.This study was conducted in one of SA’s largest hospitals to access a rich sample of participants and practitioners with experience in helping children with ASD. Parents of children with ASD, health practitioners, traditional healers and religious leaders all involved with children with a diagnosis of ASD were interviewed to explore theirexperience and understanding of the well-being of children with ASD. All data collected from the participants of the empirical component of the study were interpreted and analysed thematically following the objectives of the study. The study revealed that children with ASD are still largely exposed to an array of traditional methods of healing and religious healing methods by parents. In addition, the study found that the regulation of traditional health care and religious healing in SA is still under-regulated, which opens opportunities for untrained healers to enter the space which may cause harm to children. The study concludes that while some alternative treatments may be risky and harmful, some benefits come with using alternative methods. The study found that because traditional forms of treatment are culture-bound, they come with the benefit of a sense of hope for parents about their child’s future. Furthermore, the use of traditional alternatives creates a sense of connectedness for parents and their families. The study recommends that traditional healing and religious healing be incorporated into the health care system. The incorporation of these alternative methods may reduce the risk of children being exposed to some of the risky and harmful substances mentioned in this study and other studies conducted nationally. Also, incorporating other alternatives in the health care system may help reduce the burden experienced by the health care sector in terms of treating children with ASD. A more focused study on the evaluation of the integration process of other alternative forms of treatment into the health care system of care for children with ASD is recommended.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Bioethics and Health Law to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2021